DEVELOPMENT in vitro OF COFEE PLANTS IN DIFFERENT CULTURE MEDIUM AND PLANT GROWTH REGULATORS - JESUS, Adriana Madeira Santos; CARVALHO, Samuel Pereira de; VILLA, Fabíola; PASQUAL, Moacir; CARVALHO, Michelly (Scientia Agraria, 2010)
The nonexistence of a methodology adapted for the asexual multiplication of C. arabica in commercial scale has been the largest restriction to the employment of this technique as strategy for the use of coffee hybrid obtained by the genetic improvement. With the objective of refine the micropropagation techniques of coffee shoots, nodal segments of plants preset in vitro of C. arabica was inoculated in culture medium. In a first experiment it was studied the effect on concentrations of BAP (benzilaminopurin) and concentrations of ANA (naftalenacetic acid) on 2 cvs. In the second experiment the influence of concentrations of BAP and 2 culture medium on 3 cvs. were also verified. The pH was adjusted for 5.8 before the addition of 7 g dm-3 of agar and the sterilization to 121 ºC and 0,1 MPa for 20 min. After the inoculation, the explants was maintained in growth room at 26±1 ºC, irradiance of 32 mol m-2 s-1 and photoperiod of 16 daily hours. The experiments were a design randomized complete blocks, being used four explants by repetition and 20 plants per treatment. After 90 days, better results for cvs. Catuaí Vermelho and Maragogipe were obtained with 15 mg dm-3 of BAP. The cv. Catuai Vermelho was presented larger shoots number when compared with cv. Maragogipe. In the absence of BAP, culture medium WPM is more indicated to obtain larger number of shoots of cv. Rubi. Better results in the fresh weight of shoots were verified in culture medium MS, for cvs. Catuai Vermelho and Icatu.